You can solve this by using "similar triangles".
In triangle ABC, we are looking for side AC which is x. Side AC is similar to side DF in triangle EDF.
You can solve for side x by picking two sides in triangle ABC and their corresponding sides in triangle EDF. This is what I mean:
![\frac{AC}{BC} = \frac{DF}{EF}](https://tex.z-dn.net/?f=%20%5Cfrac%7BAC%7D%7BBC%7D%20%3D%20%20%5Cfrac%7BDF%7D%7BEF%7D%20)
Substitute for the values of AC, BC, DF and EF:
![\frac{x}{4} = \frac{11}{8} \\ \\ 8x = 4 \times 11 \\ \\ x = \frac{44}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx%7D%7B4%7D%20%20%3D%20%20%5Cfrac%7B11%7D%7B8%7D%20%20%5C%5C%20%20%5C%5C%208x%20%3D%204%20%5Ctimes%2011%20%5C%5C%20%20%5C%5C%20x%20%3D%20%20%5Cfrac%7B44%7D%7B8%7D%20)
![x = 5.5 \: units](https://tex.z-dn.net/?f=x%20%3D%205.5%20%5C%3A%20units)
To solve for y, do the same thing. Pick two sides on triangle ABC and their corresponding sides in triangle DEF.
![\frac{AB}{BC} = \frac{DE}{EF}](https://tex.z-dn.net/?f=%20%5Cfrac%7BAB%7D%7BBC%7D%20%20%3D%20%20%5Cfrac%7BDE%7D%7BEF%7D%20)
Substitute for the values and solve:
![\frac{3}{4} = \frac{y}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B4%7D%20%20%3D%20%20%5Cfrac%7By%7D%7B8%7D%20)
![4y = 24 \\ \\ y = 6 \: units](https://tex.z-dn.net/?f=4y%20%3D%2024%20%5C%5C%20%20%5C%5C%20y%20%3D%206%20%5C%3A%20units)
We have the value x to be 5.5 units and y to be 6 units.
Answer:
well you didn't show problem 11 but here is a pretty photo of Port orford Oregon
According to the given percentages, it is found that there is a 67% probability that a randomly selected man between the age of 25 and 34 does not search for green technology.
<h3>What is a probability?</h3>
A probability is given by the <u>number of desired outcomes divided by the number of total outcomes</u>.
We have that 33% of men search for green technology, hence, there is a 100 - 33 = 67% probability that a randomly selected man between the age of 25 and 34 does not search for green technology.
More can be learned about probabilities at brainly.com/question/14398287
Answer: g(f(x)) = g(x²-7)=x
Step-by-step explanation: